2019
DOI: 10.1111/nep.13578
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory renal hypertrophy following nephrectomy: When and how?

Abstract: Following surgical removal of one kidney, the other enlarges and increases its function. The mechanism for the sensing of this change and the growth is incompletely understood but begins within days and compensatory renal hypertrophy (CRH) is the dominant contributor to the growth. In many individuals undergoing nephrectomy for cancer or kidney donation this produces a substantial and helpful increase in renal function. Two main mechanisms have been proposed, one in which increased activity by the remaining ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 81 publications
0
45
0
Order By: Relevance
“…Other factors such as the nitric oxide system, the renal sympathetic nerves and the renin angiotensin system (RAS) have been implicated in the compensatory adaptations to reduction in kidney mass ( Rojas-Canales et al, 2019 ). Nitric oxide (NO), released by the endothelium, is an important vasodilator of the vasculature.…”
Section: Mechanisms Facilitating Adaptations and Potentiating Kidney mentioning
confidence: 99%
“…Other factors such as the nitric oxide system, the renal sympathetic nerves and the renin angiotensin system (RAS) have been implicated in the compensatory adaptations to reduction in kidney mass ( Rojas-Canales et al, 2019 ). Nitric oxide (NO), released by the endothelium, is an important vasodilator of the vasculature.…”
Section: Mechanisms Facilitating Adaptations and Potentiating Kidney mentioning
confidence: 99%
“…Compensatory growth is different from normal growth. At a cellular level, it is predominantly characterized by cellular hypertrophy (increased cell size and mass), and less by hyperplasia (increased cell number) 59 . Increased cell size is due to stimulated RNA and protein synthesis, which is regulated by mTORC1 (mammalian target of rapamycin complex 1) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney presents a functional reserve capacity after unilateral nephrectomy [1,2]. Many studies reported that the donor's global renal function decreased immediately after kidney donation [5].…”
Section: Discussionmentioning
confidence: 99%
“…Two main mechanisms have been proposed. One ascribes it to the increased activity of the remnant kidney that leads to hypertrophy, and the other attributes it to the release of kidney speci c factors such as insulin-like growth factor 1, epidermal growth factor and hepatocyte growth factor and pathways such as mammalian target of rapamycin in response to unilateral nephrectomy [1,8].…”
Section: Time and Mechanism Of The Renal Compensation Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation